Regional Stability for National Survival: Iran’s Foreign Policy Towards the Southern Caucasus and Central Asia in the Post-Soviet Era - Rocca, Noemi Maria (2017)
This paper focuses on Iran’s foreign policy towards the Caucasus and Central Asia regions in the post-Soviet Union era, using a theoretical approach which stresses the importance of historical and geographical contextualization for the analysis of foreign policy. The article’s main argument is that Iranian foreign policy towards these regions in the last 25 years, although the result of a complex and multi-layered decision-making process, has been led by two unifying long-term objectives: regional stability and national security. In order to demonstrate this argument, the article undertakes a factual analysis focusing on the role Iran played during the main regional conflicts that have occurred since the Soviet Union’s collapse in Central Asia and the Caucasus, as well as the diplomatic re-engagement Iran has been building with the countries of these two regions after the end of the Iran nuclear deal. Standard interpretations of Iran’s foreign policy define it as a player with hegemonic ambitions whose foreign policy is mainly led by ideological factors. This paper assumes that foreign policy’s analysis needs time and space contextualization. Once historical and geographical factors are taken into account—of which the most important are Iran’s proximity to Russia and Afghanistan along with its international diplomatic isolation due to nuclear sanctions—then Iran’s foreign policy in Central Asia and the Caucasus appears to be that of a regional power interested in maintaining the existing status quo. Stability and territorial integrity in these two regions in fact are seen by Teheran as necessary conditions for Iran’s own territorial integrity and internal security. The paper is based on both secondary and primary sources, most of them official statements, all in the public domain.